HPV, APOBEC3B, and the origins of breast cancer: a narrative review and perspectives on novel mechanisms - Liu, Zhi-yong; Chen, Ran (Frontiers in Oncology, 2026)
Breast cancer is one of the most severe global health challenges, with its incidence continuing to rise. The development of this malignancy is associated with numerous risk factors; however, its primary etiology often remains unclear. Research on the potential association between breast cancer and carcinogenic human papillomavirus (HPV) has been conducted for three decades, yet a definitive consensus has not been reached. The development of prophylactic cervical cancer vaccines has greatly heightened the urgency of this issue: if a causal relationship can be established, it would open a feasible avenue for preventing this common cancer. This review aims to systematically integrate relevant evidence and provide a critical commentary on the association between HPV and breast cancer. We analyzed evidence from 34 studies on HPV DNA detection in breast cancer cells. We discuss the prevalence and genotypes of HPV detected in breast cancer across different geographical regions, the state of the viral genome (integrated vs. episomal), viral load, and potential mechanisms for HPV-associated breast carcinogenesis—particularly its role in inducing genomic instability via activation of APOBEC3B. Additionally, we explore the histopathological and clinical characteristics of HPV-positive breast cancer. The synthesized evidence suggests that high-risk HPV types are present in a subset of breast cancers worldwide, but with lower viral loads compared to cervical cancer, indicating a potentially different mode of action. The association between HPV and breast cancer warrants further rigorous investigation to clarify its clinical and preventive implications.